2013
DOI: 10.1523/jneurosci.2211-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Microglial CD33-Related Siglec-E Inhibits Neurotoxicity by Preventing the Phagocytosis-Associated Oxidative Burst

Abstract: Sialic acid-binding Ig-like lectins (Siglecs) are members of the Ig superfamily that recognize sialic acid residues of glycoproteins. Siglec-E is a mouse CD33-related Siglec that preferentially binds to sialic acid residues of the cellular glycocalyx. Here, we demonstrate gene transcription and protein expression of Siglec-E by cultured mouse microglia. Siglec-E on microglia inhibited phagocytosis of neural debris and prevented the production of superoxide radicals induced by challenge with neural debris. Solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 18 publications
6
78
1
Order By: Relevance
“…Previous studies reported that siglec receptors bound to a wide range of sialyloligosaccharides are important regulators of innate immunity [32]. SiglecE and H expressed in mouse microglia were demonstrated to modulate phagocytosis [3335]. Therefore, we aimed to examine whether GLP modulated phagocytosis in BV2 and primary microglia was through siglec receptors.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported that siglec receptors bound to a wide range of sialyloligosaccharides are important regulators of innate immunity [32]. SiglecE and H expressed in mouse microglia were demonstrated to modulate phagocytosis [3335]. Therefore, we aimed to examine whether GLP modulated phagocytosis in BV2 and primary microglia was through siglec receptors.…”
Section: Resultsmentioning
confidence: 99%
“…Further studies are also needed to identify the putative sialic acid-modified ligands in human brain that activate CD33. Identifying these ligands might provide an approach to specifically targeting CD33 responses, though it needs to be appreciated that CD33 belongs to a related large family of sialic acid binding receptors (Siglecs), many of which have been shown also to be expressed by microglia (Claude et al, 2013;Linnartz and Neumann, 2013;Wang and Neumann, 2010). …”
Section: Discussionmentioning
confidence: 99%
“…Later, a murine monoclonal antibody was used to detect Siglec-E followed by immunoprecipitation with an anti-phosphotyrosine antibody (4G10) (12). Some commercially available antibodies have been used to detect Siglec-E in transfected Chinese hamster ovary (CHO) cells (19) and mouse microglia (20). Polyclonal Siglec-E antibody from R&D Systems (goat anti-Siglec-E) has been used in multiple studies (15)(16)(17).…”
Section: Cd33-related Siglecs Are a Family Of Proteins Widely Expressmentioning
confidence: 99%